ANALISIS IBU SINGLE PARENT DALAM MEMBENTUK DISIPLIN ANAK USIA SEKOLAH DI DESA SEGEDONG. - Prayoga, Rio; Rustiyarso, Rustiyarso; Prancisca, Stella (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to analyze the discipline formation by single mothers in raising school-aged children in the village of Segedong, Tebas Subdistrict, Sambas Regency. The sub-problems addressed in this study include how single mothers train discipline in their school-aged children at home regarding religious practices, how they train discipline in completing school assignments, and how they train discipline in assisting with household chores in the village of Segedong, Tebas Subdistrict, Sambas Regency. The research method used is descriptive qualitative research. Data collection techniques include observation, interviews, and documentation. The data collection tools used are observation guidelines, interview guides, and documentation tools. The analysis in this study is presented descriptively and qualitatively, involving 5 single mothers as informants in the village of Segedong, Tebas Subdistrict, Sambas Regency. The results of this research explain the discipline formation by single mothers in school-aged children. The conclusion drawn is that the majority of single mothers in the village of Segedong, Tebas Subdistrict, Sambas Regency have implemented discipline in their school-aged children, although they still face challenges in forming discipline in terms of religious practices, completing school assignments, and assisting with household chores.